RETRACTED: Circular RNA circ-0016068 Promotes the Growth, Migration, and Invasion of Prostate Cancer Cells by Regulating the miR-330-3p/BMI-1 Axis as a Competing Endogenous RNA - Li, Qingyuan; Wang, Wei; Zhang, Min; Sun, Wenguo; Shi, Wei; Li, Feng (Frontiers in Cell and Developmental Biology, 2020)
Prostate cancer is a common neoplasm worldwide, and the sixth most common cause of cancer-related mortality. Biomarkers for earlier diagnosis and improved treatment alternatives are critical. Circular RNAs (circRNAs) can promote the growth and progression of various cancers; however, prostate cancer-specific circRNAs have not been found. We identified circ-0016068, a circRNA that was expressed more strongly in prostate cancer tumors vs. normal paired tissue, and confirmed its relatively high expression in prostate cancer tissues and cell lines. We also discerned that circ-0016068 promotes the epithelial-to-mesenchymal transition (EMT) and the growth, migration, and invasion of prostate cancer cells in vitro; and promotes the growth and metastasis of tumors in a mouse model of prostate cancer. Moreover, we found that circ-0016068 competes with the B-lymphoma Moloney murine leukemia virus insertion region-1 (BMI-1) for binding to miR-330-3p. In so doing, circ-0016068 sequesters miR-330-3p and frees BMI-1 to enhance the proliferation, migration, and invasion of prostate cancer cells, and the metastasis of xenograft tumors. These results suggest that circ-0016068 may be a promising diagnostic biomarker for early-stage prostate cancer and a potential target for novel cancer therapeutics.